Protected Food & Wine Products as a Driving Force for Creativity and Innovation of Gastronomy Tourism Development: Case of Slovenia and Hungary - Gačnik, Aleš; Vörös, Mihály László (Agricultura Scientia, 2020)
According to world tourism statistics more than third of tourist spending is devoted to food. Over and above the high quality local food &wine have been becoming a special driving force of tourism development. Tourists have growing interests to attend gastronomic food & wine events, festivals, fairs, farmers’ markets and tasting quality food products. Gastronomy tourism is being developed as a new tourism product. Previous researches proved that a number of traditional food and wine products protected by EU or national designation have not been successfully promoted and obtained recognitions in the domestic or foreign markets. This paper aims to justify that the typical, traditional local food & wine products, as relevant gastronomy tourism attractions, need to be scientifically re-examined before promotion. It suggests new ways of gastronomy tourism promotion based on improved territorial marketing portfolio, which can create evident value added for small and medium enterprises in the sector providing an advance to move from quality to excellence.